EXPERIMENTAL AND MATHEMATICAL INVESTIGATION ON PERFORMANCE AND EMISSION CHARACTERISTICS OF OXYGEN ENRICHED AIR IN INTAKE OF A SINGLE CYLINDER DIESEL ENGINE - V, Senthil Murugan; R, Venkatachalam; M, Bharathiraja; N, Prasanna (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
ThisÂ research revealedÂ that theÂ single cylinder dieselÂ engine performance andÂ emissionÂ Â characteristics are improved by the oxygen content enrichedÂ intake air and was varied between 21% to 27 % (ie., 21,23,25,27%Â by the volume). The effects of enriched oxygen with different loads are analyzed in terms of brake thermal efficiency, specific fuel consumption, and also the environmental pollutant like NOx, CO, HC and Smoke. TheÂ Â mathematical experiment were designed using a statistical tool know as design expert based on response surface modeling. Using RSM to predict the response parameter like brake thermal efficiency, brake specific fuel consumption, carbon monoxide, hydrocarbon, nitrogen oxides and smoke. Optimization of the input and response parameters is also done using desirability approach. Finally a software tool is developed using LabVIEW software for predicting engine parameters when the engine input parameters are given.